Peralihan Fungsi Lahan Pertanian Menjadi Perumahan (Studi Kasus di Kelurahan Merjolangu, Kec. Lowokwaru, Kota Malang) - Sultan Ali Sadewa; Harsanto Nursadi (LPPM Universitas Ekasakti Padang, 2024)
The frequent conversion of agricultural land in Indonesia encourages the government to carry out or make legal products in terms of protecting sustainable food agricultural land in accordance with Law Number 41 of 2009. The stipulations in the Law are realized in the regions through the Regional Spatial Plan, in practice the conversion of agricultural land still often occurs, for example in Mojolangu Village, Lowokwaru District - Malang City. This research aims to find out whether land conversion can be implemented and how it is implemented. This research was compiled using doctrinal research methods. The results of this study are, first, the conversion of agricultural land can be carried out due to several factors, namely population, area, government policy. And regarding its implementation through the renewal of Malang City Regional Regulation Number 4 of 2011 concerning the Regional Spatial Plan of Malang City 2010-2030 which is then Malang City Regional Regulation Number 6 of 2022 concerning the Regional Spatial Plan of Malang City 2022-2042, with several stages, namely preparation for preparation, review of the previous